Mikhail Gorbachev, the human factor, and the implosion of the Soviet Union - Nunes, Daniela Pereira (2021)
Mikhail Gorbachev's unique contribution to the final balance of the Cold War and to the process that culminated simultaneously in the implosion of the Soviet Union and the failure of Soviet communism has motivated and continues to motivate scholars to think about the impact one man can have in the course of certain political processes. In the case of the Soviet Union and its disruptive process, the decisive influence of the political leader, Gorbachev, on the tragic outcome of the attempt at economic, social, and political reform seems evident. It is clear that a number of other factors, namely structural ones, influenced the events of 1985-1991, both inside and outside the Soviet Union. However, this reflection will focus on Gorbachev's role, his choices, and the limits imposed on him by the very nature of the regime he had tried to reform since 1985.